2018
DOI: 10.3389/fpsyg.2018.02352
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Eight Entrepreneurial Personality Dimensions: Validity Evidence of the BEPE Battery

Abstract: Background: The study of entrepreneurial activity has undergone intense development in recent decades. Traditionally this topic has been addressed from three approaches: economic, sociological and psychological. In the study of enterprising personality, two fundamental perspectives stand out: the use of general personality traits, like the Big Five, and the use of more specific traits related to entrepreneurial spirit, such as self-efficacy, autonomy, innovation, optimism, and others. The objective of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 48 publications
1
31
0
12
Order By: Relevance
“…Previous studies have demonstrated the scale to have good internal consistency STRUCTURE AND AUTONOMY IN JOB PERFORMANCE 11 (Leutner et al, 2014), and in the present study all four subscales had internal consistencies above α = .76 (see Table 1). META is the most widely accepted measure of entrepreneurial tendencies in the literature (Cuesta, Suárez-Álvarez, Lozano, García-Cueto, & Muñiz, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies have demonstrated the scale to have good internal consistency STRUCTURE AND AUTONOMY IN JOB PERFORMANCE 11 (Leutner et al, 2014), and in the present study all four subscales had internal consistencies above α = .76 (see Table 1). META is the most widely accepted measure of entrepreneurial tendencies in the literature (Cuesta, Suárez-Álvarez, Lozano, García-Cueto, & Muñiz, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…The development process of the CAT used the following process (Muñiz & Fonseca-Pedrero, 2019). A team of eight experts in Psychometrics constructed an initial bank of 161 items, in Spanish, designed to measure the eight specific facets defining entrepreneurial personality: self-efficacy, autonomy, innovation, internal locus of control, achievement motivation, optimism, stress tolerance, and risk-taking (Cuesta et al, 2018;Rauch & Frese, 2007). For an item to be selected, all members of the expert group had to agree on its content.…”
Section: Pool Of Items (Bepe-cat)mentioning
confidence: 99%
“…The BEPE (Cuesta et al, 2018) is a battery made up of 80 items and measures eight dimensions (10 items per dimension): self-efficacy, autonomy, innovation, internal locus of control, achievement motivation, optimism, stress tolerance, and risk-taking. These eight dimensions combine to a common factor of entrepreneurial personality.…”
Section: Pool Of Items (Bepe-cat)mentioning
confidence: 99%
“…Se han utilizado múltiples constructos de gran relevancia para poder comprender los resultados de aprendizaje, académicos y niveles de grado y logro. Enunciemos algunos de ellos que podrán ser incluidos en el muestreo de la investigación: la motivación de logro (ej., atribuciones), la autoeficacia percibida, las actitudes, las características personales, los estilos de aprendizaje y de pensamiento, el uso de estrategias, factores de inteligencia emocional, los procesos de autorregulación, entre otros, lo que permite contrastar con muchos estudios internacionales recientes en el campo, incluyendo estudios internacionales de comparación con muestras colombianas (Cheng & Lin, 2018;Cuesta et al, 2018;Díaz & García, 2016;Fang et al, 2017;García-Martín & García-Sánchez, 2017;Habok & Magyar, 2017;Mnez-Ferrer et al, 2018;Nie et al, 2017;Oriol et al, 2018;Puente et al, 2018;Robledo & García, 2018;Romera et al, 2018, Sinval et al, 2018Widlund et al, 2017). En una revisión reciente, en que se revisan todas las intervenciones pedagógicas con enfoque en la autorregulación, implementadas en China durante las últimas dos décadas, de 603 estudios, sólo pudieron incluirse en los análisis 59, y de ellos se identifican solo cuatro estudios cuasi-experimentales, frente al resto de registro de experiencias (Li, Ye, Tang, Zhou, Hu, 2018), lo que confirma el estado general a nivel, no solo de Colombia o de USA, sino generalizado, por lo que la justificación de esta investigación y con la metodología prevista, es una opción con potencial heurístico, de contribución teórica y aplicada.…”
Section: Factor De Autoevaluación Y Autorregulaciónunclassified